Human, Nation And Spirituality In A Precarious World - Atamuratov, Sadulla; Kuchkarov, Vahob; Sultonov, Asliddin (The journal of contemporary issues in business and government, 2021)
The authors critically analyze the properties of modern civilization, its achievements and certain problems of nation as a whole. The decisive criterion of development is considered high spirituality. According to the authors’ thesis, the development of science leads humankind into the abyss. It is philosophically proved that if the progress of science and technology does not harmonize with high spirituality, then such development leads humanity to disaster.